Juego simbólico y las habilidades sociales en niños de la institución educativa inicial N°728, Cabollococha 2024 - Zambrano Murayari, Lita (2025)
The essential purpose of this research was to understand and demonstrate how the level of application of symbolic play is linked to the development of social skills in children at Caballococha Early Childhood Education Institution No. 728, in 2024. This basic study, with a quantitative approach, was conducted using a non-experimental, correlational, and cross-sectional design. The participating population consisted of 95 children, whose behaviors were carefully observed using a structured guide designed as a data collection instrument. The validity of this instrument was guaranteed by a rigorous evaluation process carried out by experts specialized in education and child development. The findings revealed a significance level of less than 0.05, which allowed us to rule out the null hypothesis and support the proposed general hypothesis, thus confirming a statistically significant relationship between the practice of symbolic play and the strengthening of social skills in the institution's children. This study highlights the value of symbolic play not only as a recreational activity, but also as an essential pedagogical resource for promoting interaction, cooperation, and building empathy from the earliest years of life.